Functional Severe Acute Respiratory Syndrome Coronavirus 2 Virus-Like Particles From Insect Cells - Naskalska, Antonina; Dabrowska, Agnieszka; Szczepanski, Artur; Jasik, Krzysztof P.; Gromadzka, Beata; Pyrc, Krzysztof (Frontiers in Microbiology, 2021)
SARS-CoV-2 remains a major epidemic threat since the beginning of 2020. Efforts to combat the virus and the associated COVID-19 disease are undertaken worldwide. To facilitate the research on the virus itself, a number of surrogate systems have been developed. Here we report the efficient production of SARS-CoV-2 virus-like particles (VLP) in insect cells. Contrary to widely used pseudovirus particles, where only one coronaviral protein is displayed within a heterologous scaffold, developed VLPs are structurally similar to the native virus and allow for more throughout studies on the biology of the infection. On the other hand, being devoid of the viral genome, VLPs are unable to replicate and thus safe to work with. Importantly, this is the first report showing that SARS-CoV-2 VLPs can be efficiently produced in insect cells and purified using scalable affinity chromatography.